2016
DOI: 10.4103/1817-1737.180021
|View full text |Cite
|
Sign up to set email alerts
|

Behavior, knowledge, and attitude of surgeons and patients toward preoperative smoking cessation

Abstract: INTRODUCTION:Tobacco smoking is a well-known risk factor for postoperative complications. Quitting smoking prior to surgery helps overcome those complications.PROBLEM:Surgeons' attention for educating their patients about the importance of smoking cessation prior to surgery is one of the most effective ways to reduce smoking-related surgical complications. The extent of advised patients by their surgeons has not been identified.METHODS:A descriptive, comparative cross-sectional study using a survey was conduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 17 publications
0
16
0
Order By: Relevance
“…Initiation of smoking cessation was visible in 15.3% of our OCRs, which is a strikingly low number, considering that previous studies have found 58 to 70% of surgeons to advise their patients to quit smoking before surgery [13][14][15][16]. Insufficient training, lack of knowledge, lack of perceived efficacious interventions, and lack of time have proven the most significant smoking cessation barriers for surgeons [13,16,17].…”
Section: Discussionmentioning
confidence: 85%
“…Initiation of smoking cessation was visible in 15.3% of our OCRs, which is a strikingly low number, considering that previous studies have found 58 to 70% of surgeons to advise their patients to quit smoking before surgery [13][14][15][16]. Insufficient training, lack of knowledge, lack of perceived efficacious interventions, and lack of time have proven the most significant smoking cessation barriers for surgeons [13,16,17].…”
Section: Discussionmentioning
confidence: 85%
“…In our study, 15% of physicians were current smokers, higher than the national average (12.2%) 13 , but slightly less than the prevalence among healthcare professionals found in the western region of KSA in 2015 (18.4%) 34 . Another study assessed attitudes of surgeons practicing in KSA toward preoperative smoking cessation, and found that more than 70% of patients would like to quit smoking after surgery 35 . Almost 70% of surgeons reported that their patients quit before the surgery, however, 58.8% of patients reported not receiving advice to quit.…”
Section: Discussionmentioning
confidence: 99%
“…Almost 70% of surgeons reported that their patients quit before the surgery, however, 58.8% of patients reported not receiving advice to quit. Authors emphasized the importance of training surgeons on the negative effects of smoking on surgery outcomes 35 . Compared to the tobacco prevalence in other countries, prevalence in KSA is lower than the worldwide average (25.0%), however, it is higher than many countries that have made progress in tobacco cessation 36 .…”
Section: Discussionmentioning
confidence: 99%
“…At the surgeon’s advice, 95.3% of the patients agreed to quit smoking before surgery, 53.6% would quit after surgery, and 70.6% had already quit smoking. 36 Thorndike et al 37 evaluated physician practices regarding the counseling of patients to quit smoking, between 1991 and 1995, and found that, at 65% of visits, physicians asked patients about their smoking status; at 29%, they counseled patients to quit smoking; and, at only 1.3%, they prescribed a specific smoking cessation treatment.…”
Section: Discussionmentioning
confidence: 99%